Pengaruh Suhu dan Waktu Pengeringan terhadap Aktivitas Antioksidan dan Sifat Sensori Teh Herbal Bubuk Daun Pohpohan (Pilea trinervia W.) - Kartika Dewi, Bellariesty; Kencana Putra, I Nengah; Ari Yusasrini, Ni Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPA, 2022)
This study aimed to determine the effect of drying temperature and time on the antioxidant activity and sensory properties of pohpohan leaves herbal tea and determine the temperature and drying time that produced the highest antioxidant activity and the best sensory properties. This research was a two-factor factorial experiment with a completely randomized design (CRD). The first factor was the drying temperature (40°C, 50°C, and 60°C), and the second factor was drying time (110, 120, and 130 minutes). All treatments were repeated twice in order to obtain 18 experimental units. The data obtained were analyzed by Analysis of Variance and if the treatment had a significant effect, then continued with the Duncan Multiple Range Test. The results showed that the drying temperature of 50°C for 130 minutes was the best treatment that produced herbal tea with the following criteria: water content of 7.80%, extract content in water 22.76%, total phenol 8.65 mg GAE/g; total flavonoids 1.65, mg QE/g; IC50 value of 57.03 ppm; and panelists' acceptance for the color, aroma, taste, and overall aspects was neutral.